Pemerolehan Bahasa Anak Usia 3 Tahun pada Tataran Fonologi: Kajian Psikolinguistik - Putri, Meysi Anisa; Awwalinda, Nisa; Fatmawati, Fatmawati (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2025)
This study aims to describe the process of language acquisition in a 3-year-old child, focusing on phonological development, using a qualitative approach. Data were collected from recorded conversations and observations of the research subject, Angkasa Dexano Nugraha. A narrative analysis method was used to explore the variations in sounds produced, as well as phoneme omissions and substitutions that occurred. The results showed that Angkasa was able to produce significant sound variations, although phoneme omissions often occurred, such as the substitution of /k/ with /t/ in the word "makan" becoming "matan," and the omission of the /r/ phoneme in the word "telor" becoming "telol." These findings highlight the importance of social interaction and environmental factors in accelerating children's language development. This study provides theoretical contributions to the field of psycholinguistics by emphasizing the dynamics of language acquisition influenced by environmental and cognitive factors, as well as patterns of phoneme omissions and substitutions that reflect the child’s articulatory adaptation processes.